(untitled) (Research, Society and Development, 2025)
Common Mental Disorders (CMD) are among the mental disorders that most affect students, especially those in the health field. Studies show that the development of CMDs is multifactorial and although they are considered less serious, CMDs are related to a significant drop in students’ quality of life, affecting relationships and academic development itself. The objective of this article is to describe CMD in Brazilian medical students in their physiological and epidemiological aspects, the main risk factors involved and their variables, and the role of medical schools in this scenario, according to the literature. This is a bibliographic review of the literature with data collected through the Virtual Health Library (VHL) platform and 15 articles were included. Results were found such as: higher rate of CMD in female students, greater psychological distress in the middle of the course, lack of training in educational institutions to deal with students’ mental health, significant correlation with the course load and requirements of the medical course, abuse of legal and illicit substances and protective factors such as sports, therapy and a defined support network. It is necessary to break with prejudices about CMD by offering resources so that these students can identify and face the multifactorial nature of the problem and, thinking about the university scenario, it is necessary to implement preventive measures within colleges, in order to promote students’ mental health.